Ornithopod tracks and bones: Paleoecology and an unusual evidence of quadrupedal locomotion in the Lower Cretaceous of eastern Iberia (Teruel, Spain). (April 2023) - García-Cobeña, Josué; Cobos, Alberto; Verdú, Francisco J.
Abstract: Dinosaur tracks and osteological remains in the El Castellar Formation (upper Hauterivian–lower Barremian) in the Peñagolosa subbasin, southwest sector of the Maestrazgo Basin (Teruel Province, Spain), are scarce and fragmentary, respectively. Here, we report several unexpected, well-defined natural casts of large ornithopods from several sites of the El Castellar Formation. Moreover, an unusual manus-pes track set preserved as convex hyporelief has been found in the lowermost sandstone level of the Camarillas Formation, the first evidence of dinosaur for the base of this unit at the Peñagolosa subbasin. The ichnological comparison allows us to ascribe the studied tracks to Caririchnium . Their trackmakers were large styracosternans related to Iguanodon, and the presence of a manus-pes track set verifies that some of them may have a quadrupedal locomotion. This associated manus-pes track set constitutes one of the oldest ichnological pieces of evidence of quadrupedalism in large ornithopods from the Lower Cretaceous of Iberia and increases the limited record of this kind of track in the Lower Cretaceous of Europe. In addition, we describe some osteological fossils of these dinosaurs from the El Castellar Formation. These skeletal remains are related to medium to large-sized styracosternans, some of which closely resemble those of other European styracosternans such as Iguanodon . The evidence provided here verifies that these dinosaurs were frequent components in the coastal wetland, and fluvial to deltaic systems developed, during the late Hauterivian–early Barremian, in the Peñagolosa subbasin, possibly because these may have had a source of fresh vegetation and may have provided protection.